2013
DOI: 10.1002/ejoc.201300146
|View full text |Cite
|
Sign up to set email alerts
|

Epicoccolides: Antimicrobial and Antifungal Polyketides from an Endophytic Fungus Epicoccum sp. Associated with Theobroma cacao

Abstract: In the search for new compounds to protect plants from fungi, an endophytic fungus, Epicoccum sp. CAFTBO, obtained from Theobroma cacao was found to produce three polyoxygenated polyketides, namely epicolactone (1) and epicoccolides A (2) and B (3), together with seven known metabolites. The structures of these compounds were elucidated by a combination of detailed spectroscopic and spectrometric analyses as well as DFT calculations of the electronic circular dichroism spectra and the single‐crystal X‐ray diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
72
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(80 citation statements)
references
References 70 publications
4
72
0
Order By: Relevance
“…HMBC correlations from H 2 -1, H 2 -2, H 2 -9, H 3 -10, and H 3 -11 to C-3a and from H 2 -1, H 2 -2, and H 2 -4 to C-8a suggested the presence of a five-membered ring attached to a six-membered ring at C-3a (Figure 1). HMBC correlation from the exchangeable 8a-OH proton to C-8a (δc = 90.2 ppm) indicated that C-8a was an oxygenated sp 3 quaternary carbon attached to a hydroxy group. Moreover, the 13 C resonances of C-7 (δc = 86.6 ppm) and C-8 (δc = 82.5 ppm) suggested that both C-7 and C-8 were also oxygenated sp 3 quaternary carbons.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…HMBC correlations from H 2 -1, H 2 -2, H 2 -9, H 3 -10, and H 3 -11 to C-3a and from H 2 -1, H 2 -2, and H 2 -4 to C-8a suggested the presence of a five-membered ring attached to a six-membered ring at C-3a (Figure 1). HMBC correlation from the exchangeable 8a-OH proton to C-8a (δc = 90.2 ppm) indicated that C-8a was an oxygenated sp 3 quaternary carbon attached to a hydroxy group. Moreover, the 13 C resonances of C-7 (δc = 86.6 ppm) and C-8 (δc = 82.5 ppm) suggested that both C-7 and C-8 were also oxygenated sp 3 quaternary carbons.…”
Section: Resultsmentioning
confidence: 98%
“…We propose the name "acaciicolane" for the norsesquiterpene skeleton of 1 (Figure 3). It should be noted that, as revealed by X-ray analysis (Figure 2), a five-membered (middle) ring is perpendicular to a six-membered ring through C-7/C-8 and C-3a/C-8a bonds, and that acaciicolin A (1) possesses three consecutive oxygenated sp 3 quaternary carbons at C-7, C-8, and C-8a.…”
Section: Resultsmentioning
confidence: 98%
“…The observation, along with their 1 Hand 13 C-NMR spectra, suggested that the latter was a methyl ester of the former. Scrutiny of the 1 H-1 H COSY, ROESY, HSQC, and HMBC spectra of 3 indicated the presence of a 4,5,6-trihydroxy-7-methylisoindolin-1-one motif (27,28), which was shown to share the nitrogen atom with the 1-MT moiety (SI Appendix, Fig. S9).…”
Section: (C-23)mentioning
confidence: 99%
“…While existing in an evolutionary environment such as plant tissues, some endophytic fungi can produce the same or similar secondary metabolites as their hosts as well as other biologically active ingredients simultaneously, including new compounds (Stierle et al, 1993). Recent studies have suggested that novel natural products from endophytes displayed antibiotic effects against plant pathogens (Talontsi et al, 2013) and human tumor cell lines (Wu et al, 2013a). Therefore, they have numerous potential applications in agriculture and modern medicine, and screening for a variety of active substances from endophytic fungi has become the focus of relevant studies.…”
Section: Introductionmentioning
confidence: 99%